A second helping of gumbo for the soul : more liberating stories and memories to inspire females of color - Trotman Scott, Michelle Frazier; Walters, Nicole McZeal; Young, Jemimah L.; Ford, Donna Y. (Contemporary perspectives on multicultural gifted education., 2020)
"A Second Helping of Gumbo for the Soul is a collection of essays, stories, and narratives designed to inspire and empower women of color through the use of storytelling and narratives. This second edition is a sequel to the first Gumbo for the Soul and includes more..."--